Design of a mini fatigue bending test machine - Muhammad Hisyammuddin Md Yusof (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project focuses on the design and development of science of science and technology. Mini bending fatigue testing machine is developed based on the high cost of providing these machines in large quantities. In addition, this machine also to help the student to carry out the experiment or the test of whether learning materials in the classroom, a final year project and integrated project. The objective of this machine must be designed based on the design that is able to get power cycle the number of data and read the force applied to achieve the goal of the experiment.